PEMANFAATAN CAHAYA MATAHARI SEBAGAI SUMBER ENERGI ALTERNATIF PADA MESIN PENDINGIN UDARA MENGGUNAKAN SISTEM PANEL SURYA YANG DIRANGKAI SERI - Sulanjari, Sulanjari; Setiyono, Joko; Riyano, Hendiko Rama; Setyowati, Agustina Dyah; Irawan, Ade (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract. The purpose of this research was for analysis the performance of solar panels to operate an air conditioning machine with a capacity 220 V/ 55 W. The solar panel system consists of 2 solar panel modules which each panel has a capacity of 100 wp with a monocrystalline type connected in series. The data collection process was carried out in 2 stages, the first stage was charging the 12 V/ 65 Ah battery using a solar panel system that had been assembled with sunlight input. The measurement of the voltage increase are recorded every 30 minutes starting at 09.00 WIB until the battery is full. Then in the second stage, the battery is used to start the air conditioning machine. The measurement of the voltage decrease are recorded every 15 minutes until the battery runs out. Data collection was repeated 3 times. The research result is the value of sunlight intensity when data was collected from 09.00 to 11.30 WIB was 217.41 W/m2 and the solar panel efficiency was 47.07%. Charging time for a battery with a capacity of 12V/ 65Ah using a solar panel system takes an average of 2 hours 20 minutes with the highest battery voltage of 12.30 V. The results of charging the battery can be used to start an air conditioning machine with a capacity of 220V/ 55W for maximum time of 105 minutes with the lowest voltage of 10.25 V.Keywords: Air conditioning machine, Solar panel, Series, Battery, Sunlight